Activation of the Wnt Pathway by Small Peptides: Rational Design, Synthesis and Biological Evaluation. (29th November 2017) - Brogi, Simone; Maramai, Samuele; Brindisi, Margherita; Chemi, Giulia; Porcari, Valentina; Corallo, Claudio; Gennari, Luigi; Novellino, Ettore; Ramunno, Anna; Butini, Stefania; Campiani, Giuseppe; Gemma, Sandra
Abstract: A computational analysis of the X‐ray structure of the low‐density lipoprotein receptor‐related protein 6 (LRP6) with the Dickkopf‐1 (DKK1) C‐terminal fragment has allowed us to rationally design a small set of decapeptides. These compounds behave as agonists of the canonical Wnt pathway in the micromolar range when tested on a dual luciferase Wnt functional assay in glioblastoma cells. Two of the oligopeptides showed a lack of cytotoxicity in human primary osteoblasts isolated from sponge bone tissue (femoral heads or knees of elderly patients). According to the mechanism of action, the studies revealed a dose‐ and time‐dependent increase in the viability of human osteoblasts. These results may indicate a potential therapeutic application of this class of compounds in the treatment of bone diseases related to aging, such as osteoporosis. Abstract : A bone to pick with osteoporosis : By mimicking the DKK1 C‐terminal domain, novel oligopeptides were developed as Wnt pathway agonists. The prototypic compounds1 c and1 d, devoid of cytotoxicity, were able to dose‐ and time‐dependently increase cell viability in tests against human primary osteoblasts. These studies provide the starting point for the development of optimized potential therapeutics for the treatment of bone diseases related to aging, such as osteoporosis.